Fikih Perbandingan Hukum Pidana (Analisis Kewenangan Mahkamah Syar’iyah di Aceh dalam Sistem Hukum Pidana Republik Indonesia) - Miftahul ulum (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Syar’iyah Court has fairly broad authority other than the authority that comes from within its jurisdiction, also the authority in jinayat namely civil and criminal law, as well as mu’amalah which actually comes from the authority of the District Court, as stipulated in Qanun No. 10 2002 on the Islamic Sharia Courts, the substantive law and procedural law (the law of the event) to be used in completing the judge actions and muamalah jinayah under its authority is derived from the Shari’a. Material and formal law will be governed by the bylaws. During the substantive law and procedural law in question does not, the settlement judge actions carried out by the legislation in force. In Article 128 paragraph (2) of Law Number 11 Year 2006 concerning Aceh Government mentioned Syar’iyah Court is a court for any person who is Muslim and remain in Aceh.